Formação de biofilme em garras de gato (Felis catus) por espécies de Sporothrix spp.: um modelo ex vivo - Fernandes, Mirele Rodrigues (2021)
Sporotrichosis is a subcutaneous infection caused in most cases by traumatic inoculation of fungal propagules of pathogenic species of the genus Sporothrix, such as S. brasiliensis, S. schenckii, S. globosa and S. mexicana. It occurs in most parts of the planet, with each species having a well-defined geographic distribution. In general, contact with contaminated plant materials is the main form of infection, however it can be transmitted by animals. Currently, Brazil is experiencing an outbreak of sporotrichosis transmitted mainly by infected cats and having S. brasiliensis as the main etiological agent. Recently, the ability to form biofilms has been described in the genus. Biofilms are microbial communities associated with biotic and abiotic surfaces embedded in a polymeric extracellular matrix. They are resistant to several adverse environmental factors, such as changes in temperature and availability of nutrients, and can also act as a source of infection. Although members of the Sporothrix genus have been isolated from cat claws, little is known about how the fungus colonizes these animals. Thus, the present work seeks to analyze the biofilm formation in cat claws by species of the Sporothrix spp., using an ex vivo model. For this purpose, it was used 5 strains of S. brasiliensis, 3 strains of S. schenckii, 3 strains of S. globosa and 3 strains of S. mexicana, totaling 14 strains from the CEMM strain bank. Biofilms were incubated for 7 and 15 days, at 28 ° C. The formation of biofilms was confirmed by scanning electron microscopy (SEM) images. Metabolic activity was measured using the XTT reduction assay. All strains analyzed were able to form biofilm on cat claws. The analysis of metabolic activity showed that the 7-day period was the optimum time to produce biofilms ex vivo. The biofilms formed had morphology and metabolic activity similar to those found in the in vitro model, with no significant differences between species. The formation of biofilms from species of Sporothrix spp. in cat claws it can be an important factor in the transmission and dispersion of fungi, similarly to that seen in Candida auris biofilms in human skin, and it can generate hypervirulent cells. Subsequent analyzes with in vivo models and on gene expression in biofilms formed on claws can provide important information about the disease transmission cycle and the role of biofilms in it.